Pulmonary Function and Persistent Clinical Symptoms in Children and Their Parents 12 Months After Mild SARS-CoV-2 Infection - Bode, Sebastian F. N.; Haendly, Marisa; Fabricius, Dorit; Mayer, Benjamin; Zernickel, Maria; Haddad, Anneke Donne Maree; Frieh, Pauline; Elling, Roland; Renk, Hanna; Stich, Maximilian; Jacobsen, Eva-Maria; Debatin, Klaus-Michael; et al. (Frontiers in Pediatrics, 2022)
Background Pulmonary involvement is the leading cause of morbidity and mortality after severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. Long-term impairment has been reported in adults with severe infection. However, most infections cause only mild symptoms or are even asymptomatic, especially in children. There is insufficient evidence regarding pulmonary outcome measures in mild SARS-CoV-2. The objectives of this study were to determine spirometry parameters after SARS-CoV-2 infection and correlate those with reported persisting symptoms in children, adolescents, and adults. Methods Data on clinical symptoms during acute infection as well as SARS-CoV-2 serology results were recorded. Twelve months after infection, spirometry was performed and information on persisting symptoms was collected using a structured questionnaire. 182 participants (108 SARS-CoV-2 positive) from 48 families were included; 53 children (< 14 years), 34 adolescents and young adults (14–25 years), and 95 adults. Results Spirometry values did not significantly differ between the particular subgroups of the cohort (adults, adolescents, children; infected and non-infected individuals). Adults reported more symptoms during acute infection as well more persisting fatigue (29.7% of participants), reduced physical resilience (34.4%), and dyspnea (25.0%) 12 months after infection than adolescents (fatigue 26.7%, reduced physical resilience 20%, and 0% dyspnea) and children (4%, 0%, 0%, respectively). There was no correlation between persistent subjective symptoms and spirometry results. Discussion Children and adolescents are less affected than adults by acute SARS-CoV-2 as well as by post-infection persistent symptoms. Spirometry was not able to demonstrate any differences between healthy individuals and participants who had suffered from mild SARS-CoV-2 12 months after the infection.